2008
DOI: 10.3748/wjg.14.1925
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of common CFTR polymorphisms poly-T, TG-repeats and M470V in a healthy Chinese population

Abstract: Huang Q, Ding W, Wei MX. Comparative analysis of common CFTR polymorphisms poly-T, TG-repeats and M470V in a healthy Chinese population. World J Gastroenterol 2008; 14(12): 1925-1930 INTRODUCTIONThe cystic fibrosis transmembrane conductance regulator (CFTR) gene on chromosome 7q31 spans approximately 250 kb of DNA and encodes 27 exons encodes [1] . The CFTR gene encodes a cAMP-and ATP-dependent chloride channel that is present in the apical membrane of the epithelial cells that line most exocrine glands [2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…The results of the analysis of three previously determined polymorphic loci by frequency of alleles was consistent with previous reports of the frequencies of poly-T, TG-repeats, and M470V CFTR mutations in healthy Chinese populations[12]. These findings are also supported by a multitude of previous studies that suggest that while the frequency of these polymorphisms was quite different in the Caucasian populations, little variation was found in the East Asian populations[15][17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the analysis of three previously determined polymorphic loci by frequency of alleles was consistent with previous reports of the frequencies of poly-T, TG-repeats, and M470V CFTR mutations in healthy Chinese populations[12]. These findings are also supported by a multitude of previous studies that suggest that while the frequency of these polymorphisms was quite different in the Caucasian populations, little variation was found in the East Asian populations[15][17].…”
Section: Discussionsupporting
confidence: 90%
“…Previous study has yielded critical information related to the polymorphism of poly-T, TG-repeats, and M470V in healthy Chinese populations[12]. In an effort to expand the scope of these observations, the present study was to investigate the specific impact of poly-T, TG-repeats, and M470V CFTR variations on susceptibility of a representative Chinese Han population in Jiangsu Province to bronchial asthma and chronic bronchitis.…”
Section: Introductionmentioning
confidence: 99%
“…The TG repeats and poly-T tract can influence CFTR at transcription levels because these intronic variants could lead to reductions in protein synthesis and expression, or altered splicing to compromise the intracellular transport and/or activity. Huang et al 29 conducted the first comprehensive study on the functional polymorphisms of CFTR in Chinese healthy subjects and found that T7 was the most common haplotype (93.6%) and (TG)11 and (TG)12 were the dominant haplotypes in the junction of intron 8 and exon 9. Our current data also validated (TG)11-T7 as the most common type.…”
Section: Discussionmentioning
confidence: 99%
“…The T 7 allele is the most frequent in normal individuals with an approximate frequency of 80% in Caucasians [28,29] and 90% in East Asians [30]. However the frequency of poly T polymorphism in CF patients is controversial in different population studied.…”
Section: Introductionmentioning
confidence: 99%